A Ciência da Informação no contexto da pós-graduação do IBICT - (:unkn) unknown (Ufrj : Ibict, 1995)
Relata o surgimento do curso de pós-graduação (Mestrado) em Ciência da Informação do Ibict, e do curso de Documentação Científica/Curso Especialização Informação e Documentação (CDC). Analisa a origem das disciplinas que constituem o currículo. Apresenta uma visão internacional e local (IBICT/DEP) das mudanças da Ciência da Informação. [en] The emergence and development of the Master Course in Information Science and the Specialized Course in Information and Documentation of the Brazilian Institute for Information Science and Technology (IBICT) is described here. The origin and the charactheristics of courses and curriculum are analysed. An international and local (IBICT/DEP) perspective of changes in the Information Science field is presented.
Keywords: Pós-graduação; Ciência da Informação; Ibict